Relação entre a doença periodontal e doença cardiovascular: há uma preocupação por parte dos que fazem clínica médica e odontológica na cidade de Natal? - Maia, Alexandre Pinto (2007)
The relationship between periodontal and cardiovascular diseases is a reality in the current days. The knowledge about the role of periodontal disease as a risk factor to cardiovascular disease from dentistry and physicians is very important to try to eliminate this risk factor. The aim of this work was to investigate, using a questionary, if physicians and dentistry are aware about this relationship and if they think that it is important. These forms were distributed in 4 groups: cardiologists (n=90), physicians from other specialist (POS) (n=110), periodontists (n=35) and dentistry from other specialist (DOE) (n=85). We had a loss off 32,4% of the total sample due to a lack of response of some professionals. Our results showed that all cardiologists, all dentists and 68,2% of POE said that they had gotten information about the relationship between periodontal and cardiovascular disease, and just 6 POS don t believe that this relationship can occur. When questioned if, even when a periodontal disease is diagnosed, there is a habit to treat or orient the patient for treatment, 29,5% of cardiologists answered no, 25,5% of POE also answered that they did not orient and only 1 DOE answered that he did not treat nor orient. All periodontists said that treat their patients when periodontal disease was identify. The physicians seem not to find important the relationship that exist between periodontal and cardiovascular diseases and the dentistry have shown a good knowledge about this subject. Maybe, if physicians and dentistry work together, the incidence of cardiovascular disease decreases